2023
DOI: 10.3390/jcm12041551
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport after Adolescent Idiopathic Scoliosis (AIS) Correction Surgery: A Retrospective Data Analysis

Abstract: Sports are relevant to younger populations in society. Adolescent idiopathic scoliosis (AIS) patients who undergo surgical correction of the spine are often intensively involved in sports. For that, returning to the sport is often an important concern for the patients and their families. To the best of our knowledge, there is still a lack of scientific data indicating established recommendations about the time of returning to sport activities after surgical spinal correction. The aim of this study was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…However, in some patients, especially after extremely long spine fusion, the loss of mobility could make it difficult for patients to play at the same level as preoperatively. According to Pepke et al [14], 29.2% of a series of 33 patients operated of spinal fusion for AIS could return to the same level of preoperative sport activity. Many patients in this study who resumed sports postoperatively shifted from contact sports toward lower level and intensity sports activities.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some patients, especially after extremely long spine fusion, the loss of mobility could make it difficult for patients to play at the same level as preoperatively. According to Pepke et al [14], 29.2% of a series of 33 patients operated of spinal fusion for AIS could return to the same level of preoperative sport activity. Many patients in this study who resumed sports postoperatively shifted from contact sports toward lower level and intensity sports activities.…”
Section: Discussionmentioning
confidence: 99%
“…There is a small body of evidence surrounding safety of when it is appropriate for an individual to return to sports, exercise, or physical activity following corrective surgery in AIS (23,24,88). However, there remains very little information regarding rates of participation and uptake of sports, exercise, and physical activity (21,27).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence to suggest no difference in restrictions towards sporting activity following spinal fusion compared to nonoperative treatment (21). Whilst the majority of routine practice encourages exercise following spinal surgery for AIS, individuals are usually advised to avoid contact sports post-operatively (22)(23)(24). Individuals with AIS who regularly participate in physical activity have improved HRQOL, physical and mental wellbeing, and self-esteem (6,17,25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Kinesiotherapeutic treatment [8,9] and bracing [10][11][12][13] for improving the proper body posture, in the majority of IS patients provide only partial benefits for slowing down the progression of the pathological curvature. Negrini et al [14,15] concluded on the necessity for surgical intervention in IS patients with a primary Cobb angle of 40-45 degrees when a fast worsening of the pathology is expected.…”
Section: Introductionmentioning
confidence: 99%